The pursuit of happyness / [Video recording] (Culver City, CA : Columbia Pictures Industries, 2007)
Chris Gardner is an intelligent, energetic guy who can't catch a break. In the sluggish Bay Area economy of 1981, he's losing ground, by investing all his family's money in high cost bone-density scanners. His wife leaves him, he loses his apartment, and with his 5-year-old son in tow joins the ranks of the homeless, if not the hopeless. Bounced from shelter to shelter, he finds himself a single dad who has to support and care for a young child. Impressing a Dean Witter higher-up by solving a Rubik's cube during a taxi ride, Chris gets a place in a stockbroker-training program. But internships don't pay, and there's no guarantee he'll be offered a job at the end of it. Against all odds, he pushes toward success, and eventually turns his life around.